Comparative Analysis of the Level of Hygienic Dental Knowledge of Hard of Hearing and Hearing Disabled People in the City of Penza and the Penza Region - Marina Suvorova; Anna Belousova; Galina Emelina; Anna Teplova (Journal of Global Pharma Technology, 2020)
Modern health care has a set of problems. Our native medicine is in great need in the socially oriented help to different groups of the population of the country. One of socially unprotected groups is hard of hearing persons. The special social status does this contingent of the population especially vulnerable in the questions of stomatologic education. It involves the low level of hygienic stomatologic knowledge, and also insufficient motivation to preservation and promotion of an oral cavity health. In Russia there aren't enough researches devoted to the appreciation of the preventive stomatologic help level and to the specified contingent’s needs in it. Creation of the program of prevention of stomatologic diseases of hard of hearing persons is one of the important problems of stomatology. It is available for their specific world’s perception. Relevance is caused by the high level of distribution of stomatologic pathologies among hard of hearing persons of Penza region. Keywords: Hard of hearing persons, Stomatologic education, Hygiene of an oral cavity, Prevention of stomatologic diseases.